CALCULATION OF OPERATION FEE FOR ROMANIAN RAILWAY INFRASTRUCTURE - Stefan IOVAN; Profir IONITA; Marcel LITRA (Fiabilitate şi Durabilitate)
Fees charging for railways capacity (infrastructure, stations, signaling, etc.) is a mechanismthat allows different users of railway services to have access to the rail network under fair conditions.This mechanism allows rail operators to offer new services, to improve choice and quality of railtransport offer and to encourage those who operate them, under the effect of competition, to lower costsand improve services quality. Meanwhile, in a vertically integrated rail system, the integrated railwaycompany is not excited to authorize new users to use its network, thus entering into competition with itsown services. Difficulties in implementing this type of relationship between integrated railway companiesand other stakeholders have led in Europe, especially under the influence of the European Union(Directive 91/440), to the separation of operational railway infrastructure, first in terms of accountingand then, more and more, functionally. The Infrastructure Operation Fee (IOF) is an annual fee,monthly paid, which gives a railway passenger or freight operator the right to operate on ownedproperty or on property managed by National Railway Company CFR SA (CFR). This fee will cover fixand variable costs (caused by the movement of trains on infrastructure and taking into accountinfrastructure improvements and constructions performed for this purpose) and provide an acceptablerate of return.